SPECIES DIVERSITY OF SOIL FUNGI FROM A CORN PLANTATION AT ECHAGUE, PHILIPPINES - Rey Mark Gascon Tecson; Florenda C. Ballesteros - Temanel; James Kennard Sanz Jacob (Biotropia: The Southeast Asian Journal of Tropical Biology, 2021)
Soil fungi are a critical component of the agroecosystems and provide ecological services that affect food and bio-product production. Awareness of the composition and distribution of local species is necessary to maximize the productivity and sustainability of the agroecosystems. This study aimed at isolating fungi from the soil samples collected from a corn plantation at Echague, Isabela, morphologically defining, characterizing, and determining the diversity of fungal isolates species. Soil samples from five (5) different sampling units were collected and microbiological techniques were used to isolate the fungi. Identification was performed by morphological characterization of fungal isolates guided by taxonomic keys and textbooks. Fungal diversity was assessed using Simpson's indices of diversity. Sixteen (16) fungal isolates were found; 12 were known and four (4) were unidentified. Ten (10) species belong to the Ascomycota group, and two (2) belong to the Zygomycota class. The Aspergillus species dominated the region amongst all the species isolated and established. Aspergillus fumigatus and Aspergillus flavus are densely populated and well distributed. A potent biocontrol agent was also identified, namely Trichoderma harzianum and Trichoderma viride. The Mucor sp. and the Rhizopus stoloniferous, Zygomycota fungi, were also identified.